Serum Matrix Metalloproteinase-3 in Comparison with Acute Phase Proteins as a Marker of Disease Activity and Radiographic Damage in Early Rheumatoid Arthritis. (7th April 2013) - Ally, Mahmood M. T. M.; Hodkinson, Bridget; Meyer, Pieter W. A.; Musenge, Eustasius; Tikly, Mohammed; Anderson, Ronald
Abstract : Matrix metalloproteinase-3 (MMP-3) is involved in the immunopathogenesis of rheumatoid arthritis (RA), but little is known about its relationship to genetic susceptibility and biomarkers of disease activity, especially acute phase reactants in early RA. MMP-3 was measured by ELISA in serum samples of 128 disease-modifying, drug-naïve patients and analysed in relation to shared epitope genotype, a range of circulating chemokines/cytokines, acute phase reactants, autoantibodies, cartilage oligomeric protein (COMP), and the simplified disease activity index (SDAI). MMP-3 was elevated >1.86 ng/ml in 56.25% of patients (P < 0 . 0001 ), correlated with several biomarkers, notably IL-8, IL-6, IFN γ, VEGF and COMP (r values = 0.22–0.33, P < 0.014 –0.0001) and with CRP and SAA levels (r = 0.40 and 0.41, resp., P < 0.0000 ) and SDAI (r = 0.29, P < 0.0001 ), but not with erosions or nodulosis. However, the correlations of CRP and SAA with SDAI were stronger (respective values of 0.63 and 0.54, P < 0.001 for both). COMP correlated with smoking, RF, and MMP-3. MMP-3 is significantly associated with disease activity, inflammatory mediators and cartilage breakdown, making it a potential biomarker of disease severity, but seemingly less useful than CRP and SAA as a biomarker of disease activity in early RA.